USES OF ADMINISTRATIVE DATA AT THE SOCIAL SECURITY ADMINISTRATION. - McNabb, Jennifer; Timmons, David; Song, Jae; Puckett, Carolyn (Social Security Bulletin, 2009)
The Social Security Administration (SSA) collects a wealth of data in its role as administrator of two large national entitlement programs. Linking SSA's administrative data with survey data yields a broader set of demographic and socioeconomic information and also improves the quality of the survey data. The agency uses these data to produce analyses and research on policy initiatives for its programs and on the earnings of the working and beneficiary populations. SSA studies how these programs and potential changes to them affect individuals, the economy, and program solvency, and develops models to project demographic and economic characteristics of the current working population into the future. The agency also produces public-use microdata files that are available to outside researchers, as well as a variety of research and statistical publications to inform policymakers and the public.